2012
DOI: 10.1063/1.3676254
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, dielectric and spectroscopic studies on MnO doped LiI–AgI–B2O3 glasses

Abstract: LiI-AgI-B 2 O 3 glasses doped with different concentrations of MnO (ranging from 0 to 0.8 mol%) were prepared. Electrical and dielectric properties have been studied over a wide frequency range of 10 À2 -10 6 Hz and in the temperature range from 173 to 523 K. The valence states of manganese ions and their coordination in the glass network have been investigated using optical absorption, luminescence, and ESR spectroscopy. The analysis of the spectroscopic results has indicated that the manganese ions exist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…Indeed, it has been reported that the g-factor of MnO doped glass samples increases with the MnO concentration [30]. This behavior, however, was not exhibited by the samples studied in this work.…”
Section: A N U S C R I P Tcontrasting
confidence: 60%
“…Indeed, it has been reported that the g-factor of MnO doped glass samples increases with the MnO concentration [30]. This behavior, however, was not exhibited by the samples studied in this work.…”
Section: A N U S C R I P Tcontrasting
confidence: 60%
“…1a) show that the intensity of these bands (350, 410 and 510 nm) and the PZABP: 0.8Mn sample (top spectrum) increases as x concentration increases. These bands (350, 410, and 510 nm) have also been observed in Mn:YAlO 3 crystals (Noginov and Loutts 1999), in LiI-AgI-B 2 O 3 (Wan et al 2014), and SrO-Al 2 O 3 -B 2 O 3 -SiO 2 glass systems doped with different levels of MnO (Milankovic et al 2012) and in MnO single crystals (Mochizuki et al 1992). The bands (350, 410, and 510 nm) are identified as 4 A 2 ( 4 F) ?…”
Section: Resultsmentioning
confidence: 73%
“…As a result charge carries are accumulated near the electrodes and cause large space near-surface charge polarization. The observed higher values of ε′(ω) at higher temperatures and at a lower frequency are obviously because of this polarization [19]. At a higher frequency, the charge carriers may not be able to rotate sufficiently rapidly and hence, their oscillation will begin to lay behind this field leading to a decrease of dielectric permittivity, ε′(ω).…”
Section: Ionicsmentioning
confidence: 83%
“…2b variation of ε′(ω) with temperature for the same glass sample is presented. At higher frequency, ε′(ω) approaches to a constant value, ε′ ∞ (ω), which results in a rapid polarization processes occurring in the glasses under applied field [18,19]. With decreasing frequency dielectric constant reaches higher value, ε′ s (ω).…”
Section: Resultsmentioning
confidence: 99%